2009
DOI: 10.1007/s00792-009-0268-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activity and diversity during extreme freeze–thaw cycles in periglacial soils, 5400 m elevation, Cordillera Vilcanota, Perú

Abstract: High-elevation periglacial soils are among the most extreme soil systems on Earth and may be good analogs for the polar regions of Mars where oligotrophic mineral soils abut with polar ice caps. Here we report on preliminary studies carried out during an expedition to an area where recent glacial retreat has exposed porous mineral soils to extreme, daily freeze-thaw cycles and high UV fluxes. We used in situ methods to show that inorganic nitrogen (NO(3) (-) and NH(4) (+)) was being actively cycled even during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 65 publications
1
53
0
Order By: Relevance
“…The experiment shown in Figure 4 was done in low volumes of growth media so that they froze every night and completely melted every day. To our knowledge, this is the first demonstration of the growth of any microbe during extreme freeze-thaw cycles, although activity of microbes during such cycles has long been known (reviewed in Schmidt et al 2009a). The ability to survive and thrive within a very broad temperature range may be a characteristic widespread within the Tremellomycetes; even pathogenic Cryptococcus gatti and C. neoformans exhibit broad tolerance to a range of temperatures (Nichols et al 2007, Garcia-Solache and Casadevall 2010), but have not been shown to be able to grow at subfreezing or fluctuating temperatures like members of the genus Naganishia .…”
Section: Ecological Tolerances Of Naganishiamentioning
confidence: 86%
“…The experiment shown in Figure 4 was done in low volumes of growth media so that they froze every night and completely melted every day. To our knowledge, this is the first demonstration of the growth of any microbe during extreme freeze-thaw cycles, although activity of microbes during such cycles has long been known (reviewed in Schmidt et al 2009a). The ability to survive and thrive within a very broad temperature range may be a characteristic widespread within the Tremellomycetes; even pathogenic Cryptococcus gatti and C. neoformans exhibit broad tolerance to a range of temperatures (Nichols et al 2007, Garcia-Solache and Casadevall 2010), but have not been shown to be able to grow at subfreezing or fluctuating temperatures like members of the genus Naganishia .…”
Section: Ecological Tolerances Of Naganishiamentioning
confidence: 86%
“…In the Sierra Nevada Mountains, USA, Sickman et al (2003) and earlier studies by Brooks et al (1996Brooks et al ( , 1997 in the Colorado Front Range of the Rocky Mountains provide strong evidence that microbiological processes may also explain the observed increased N export from high-elevation catchments. Surprisingly, Schmidt et al (2009) showed that significant nitrification occurs in recently deglaciated soils even on days when the soil temperature (at 5 cm depth) ranged from −10 • C at night to +30 • C during the day. Highelevation areas with little or no developed soils have shown large amounts of microbial activity (King et al, 2008;Nemergut et al, 2007), within a few years of deglaciation in some cases .…”
Section: N Mladenov Et Al: Atmospheric Deposition As a Source Of Camentioning
confidence: 97%
“…Both the North Pole and South Pole were reached four decades before the highest peak in the world, Mount Everest, was climbed in 1953. The highest soil ecosystems on Earth are characterized by low oxygen pressure, low levels of available water, high levels of radiation and extreme temperature cycling across the freezing point [2,4]. These physical extremes in turn lead high-elevation soils and sediments to be low in nutrients and ostensibly devoid of measurable life.…”
Section: Introductionmentioning
confidence: 99%
“…These physical extremes in turn lead high-elevation soils and sediments to be low in nutrients and ostensibly devoid of measurable life. However, recent work in the high Andes has shown greater than expected microbial biomass and biogeochemical cycling of nutrients even in undeveloped soils just below the permanent ice line [4,5]; but almost nothing is known about the responsible organisms or their global biogeographic distribution, especially in the highest mountains on Earth, the Himalayas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation